Pengaruh Kepribadian (Big-Five Personality) dan Ketekunan (Persistence) terhadap Interpersonal Citizenship Behavior Peserta Didik SMAN di Jakarta - Salsabila Tasyari (IJEEM - Indonesian Journal of Environmental Education and Management, 2023)
Environmental problems are increasingly complex and threaten the balance of the environment. This happens when humans do not pay attention to the environmental balance. The aim of this research is to know the effect of personality and persistence on interpersonal citizenship behavior. This research was conducted on 100 students at SMAN 59 Jakarta in the odd semester of the 2022/2023. The method used is a survey method through casual studies and analyzed by path analysis. The result of the calculation of the interpersonal citizenship behavior reliability coefficient is 0.943, the persistence is 0.933,and the big-five personality is 0.956 which indicates that the instrument can be trusted. The results showed that personality directly affected interpersonal citizenship behavior very significant, persistence directly affected interpersonal citizenship behavior very significant, big-five personality directly affected persistence very significant, and big-five personality had an indirect effect on interpersonal citizenship behavior through persistence significantly.